Intellect beyond Law: The Case of Legal Education - Gross, Peter W. (1985)
Conceptions of intellect long basic to Western academic thought increasingly are being called into question. These conceptions, which equate intellect with finding and applying the laws that govern phenomena, have been seen to divorce us from realities of choice and self-creation that underlie the human experience. The first half of the Article develops these themes, suggesting the philosophical and practical importance of alternative, more expansive conceptions of intellect. The second half then illustrates these points, using legal education as a case study